Overview of Indian Hyrtanellini (Ephemeroptera: Ephemerellidae), with new species and records from related regions - Martynov, Alexander V.; Selvakumar, C.; Subramanian, K. A.; Sivaramakrishnan, K. G.; Vasanth, M.; Sinha, Bikramjit; Jacobus, Luke M. (Zootaxa, 2021)
The Hyrtanellini (Ephemeroptera: Ephemerellidae: Ephemerellinae) from India and related regions are reviewed, including three new species viz., Serratella palatovi Martynov, Selvakumar & Jacobus, sp. nov., Torleya simbalbarensis Selvakumar, Subramanian, Martynov & Jacobus, sp. nov., and Torleya dibruensis Selvakumar, Martynov & Jacobus, sp. nov.; and first country records of Teloganopsis jinghongensis (Xu, You & Hsu, 1984) and Hyrtanella grandipennis (Zhou, Su & Gui, 2000). Description of Serratella palatovi sp. nov. is based on material from Thailand, India and Nepal; Torleya simbalbarensis sp. nov. and Torleya dibruensis sp. nov. are described based on material from India. For now, the tribe Hyrtanellini in India comprises eight species from the genera Serratella Edmunds, 1959, Torleya Lestage, 1917, Teloganopsis Ulmer, 1939 and Hyrtanella Allen & Edmunds, 1976. Additional records of Teloganopsis jinghongensis from Thailand, Torleya nepalica (Allen & Edmunds, 1963) and Torleya coheri (Allen & Edmunds, 1963) from Nepal also are provided here. All Indomalayan Hyrtanellini species are discussed to some extent.